ELECTRONIC CONTRACT MANAGEMENT AND ITS INFLUENCE ON PERFORMANCE OF STATE CORPORATIONS IN KENYA - Linus Ndege Murithi; Patrick Karanja Ngugi; David Kiarie (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
State corporations are instrumental in dispensing the government’s functions and mandates, thus streamlining economic growth and development. With procurement being responsible for the largest portion of government’s spending, state corporations spend a significant amount of state resources. These agencies, however, continue to record a decline in performance despite being the biggest consumers of government revenue. The agencies have been blamed for inefficiency and poor integration of technological systems in their procurement processes, leading to gaps that see inefficiencies and ineffective management of public funds. While integration of electronic procurement in these corporations has been explored, key aspects of e-procurement such as electronic contract management remain under-explored. This study examined the extent to which state corporations have embraced electronic contract management and whether it has contributed to their performance. Descriptive correlation research design was adopted. The study targeted supply chain managers from 248 state corporations in Kenya. Using a sampling formula, a sample of 153 respondents was obtained and selected through a stratified random sampling technique. A questionnaire used to collect data for the study, which was analyzed using descriptive and inferential statistics. The findings revealed that electronic contract management significantly influenced performance of state corporations in Kenya. It was concluded that most of the corporations had not effectively embraced electronic contract management and this affected their performance. It is therefore recommended that the state corporations through the management ought to integrate electronic systems in managing contracts as a way of promoting effectiveness and efficiency in contract implementation. Keywords: Electronic Procurement, electronic Contract Management, Organizational Performance, state Corporations